CLINICAL STUDY OF EFFICACY OF VATSAKADI YOGA IN PRAVAHIKA - Irayya Swami, *Santosh; Dakhode, Vrushali V. (International Journal of Ayurveda and Pharma Research, 2016)
Background: Todays busy scheduled and fast lifestyle is prone for many gastrointestinal disorders. People use to take fast food, junk food. Also due to lack of exercise and sedentary work digestion tends to be hampered. Mental stress is also one of the main reason behind it. Pravahika (Amoebiasis)is one of the major disease of gastrointestinal tract. Due to Nitya hetusevana (aetiological factors), Pravahika recurrence is more although antibiotics are widely and routinely used for its management. In Ayurveda various modalities are given but Vatsakadi yoga is supposed to give major relief with respect to signs and symptoms of Pravahika. Aim: To evaluate the efficacy of Vatsakadi yoga in Pravahika. Materials and Methods: It was an open randomized parallel group trial. Total 30 patients were treated out of which 15 patients were treated with Vatsakadi yoga and 15 patients with standard drug Balbilva choorna. Results & Conclusion: Individually both groups have given relief in cardinal signs and symptoms of Pravahika. While comparing, it was also statistically proved that Vatskadi yoga is more effective in the management of Pravahika than Balbilva choorna with respect to signs and symptoms of Pravahika.